Reflections on humanizing education for Economics and Management Sciences - Abdul Razak, Dzuljastri (Kulliyyah of Economics and Management Sciences IIUM, 2021)
This book compiles 15 written expressions of the participants of 2021 KENMS ‘Ibadah Camp with the theme “attributes of true believers in the Qur’an and Sunnah” within the framework of humanizing education with Maqasid al-Shari’ah. The attributes of true believers should be rooted in spirituality.